Impact of Catharanthus roseus leaf ethanol extract on survival, growth and development of Dysdercus koenigii(Heteroptera: Pyrrhocoridae) - Mohd Shazad; Sunil Kayesth
The effects of Catharanthus roseus leaf ethanol extract (Cr-LEE) on the survival, growth, and development of Dysdercus koenigii Fabricius were studied. The experiments were conducted on 0-12 hour-old fifth instar nymphs reared and maintained in the laboratory under optimum conditions. Catharanthus roseus leaf ethanol extract (Cr-LEE) was applied topically at doses 40, 100, 200, and 400 (So(Bg/Insect to the fifth instar nymphs. The results indicate that treating fifth-instar nymphs with Cr-LEE affected their survival and development. The effects on survival, growth, and development were dose-dependent. Treatment at doses 200 and 400 (So(Bg/Insect shows high mortality, especially during the later part of their life. Different developmental anomalies, such as supernumerary nymphal stage, adultoid, adult with deformed wings, adult with exuviae attached to different parts of the body, and adult with shrunken body, were observed. Often, the nymphs died due to abortive moulting. The gas chromatography and mass spectroscopy (GC-MS) analysis of the Cr-LEE revealed the presence of chemical compounds having insecticidal and insect-repellent activity and compounds that are intermediate in the juvenile hormone (JH) biosynthetic pathways. These compounds may act as JH mimics or Juvenoids for insect pests. Therefore, it is apprehended that the phytoconstituents of Cr-LEE singly or synergistically affect the survival, growth and development of D. koenigiis